Ionic liquid-assisted in situ growth of a cobalt oxide composite and its application in supercapacitors and electrochemical biosensors. (25th October 2018) - Li, Fajun; Ruan, Chaohui; Wang, Yang; Lei, Lixu
Abstract : [C16 MIM]CF3 COO and GO were used as template and 2D planar substrate for in situ growth of Co3 O4 NR-P/GO. Abstract : Cobalt(ii, iii ) oxide (Co3 O4 ) nanorods/reduced graphene oxide (Co3 O4 NR/RGO) composite has been successfully prepared via a reactable ionic liquid-assisted hydrothermal process and subsequent annealing. Here, the ionic liquid 1-hexadecyl-3-methylimid-azolium trifluoroacetate ([C16 MIM]CF3 COO) has been used as the template, co-solvent and reactant. Co3 O4 NR/RGO can be used as the electrode material in supercapacitor applications and the non-enzymatic electrochemical detection of glucose. It has been found that the Co3 O4 NR/RGO composite displays superior capacitive performance not only with high specific capacitance of 813.1 F g −1 at a current density of 1 A g −1, but also with excellent cycling stability. It can even detect glucose with a high sensitivity of 81.8 μA mM −1 and a remarkable low detection limit of 67 nM (S/N = 3).